2009
DOI: 10.1111/j.1742-4658.2008.06836.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β protofibril levels correlate with spatial learning in Arctic Alzheimer’s disease transgenic mice

Abstract: Oligomeric assemblies of amyloid‐β (Aβ) are suggested to be central in the pathogenesis of Alzheimer’s disease because levels of soluble Aβ correlate much better with the extent of cognitive dysfunctions than do senile plaque counts. Moreover, such Aβ species have been shown to be neurotoxic, to interfere with learned behavior and to inhibit the maintenance of hippocampal long‐term potentiation. The tg‐ArcSwe model (i.e. transgenic mice with the Arctic and Swedish Alzheimer mutations) expresses elevated levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 45 publications
6
70
1
Order By: Relevance
“…Analysis for spatial learning and memory, however, revealed that 12-month-old mice with readily detectable ADDLs displayed a significant delay in acquisition when compared with non-transgenic littermates [31]. Aβ protofibril levels correlate with spatial learning in AD transgenic mice expressing human APP with the Arctic mutation [32], facilitating early intraneuronal Aβ aggregation [33]. Despite the difficulty in comparing the different studies on oligomeric Aβ species there seems to be converging evidence that they (i) are primarily formed within neurons, (ii) oligomeric Aβ species are more neurotoxic than monomeric or fibrillar Aβ in vitro, (iii) oligomeric Aβ species decrease synaptic activity.…”
Section: Role Of Soluble Oligomers and Protofibrilsmentioning
confidence: 91%
“…Analysis for spatial learning and memory, however, revealed that 12-month-old mice with readily detectable ADDLs displayed a significant delay in acquisition when compared with non-transgenic littermates [31]. Aβ protofibril levels correlate with spatial learning in AD transgenic mice expressing human APP with the Arctic mutation [32], facilitating early intraneuronal Aβ aggregation [33]. Despite the difficulty in comparing the different studies on oligomeric Aβ species there seems to be converging evidence that they (i) are primarily formed within neurons, (ii) oligomeric Aβ species are more neurotoxic than monomeric or fibrillar Aβ in vitro, (iii) oligomeric Aβ species decrease synaptic activity.…”
Section: Role Of Soluble Oligomers and Protofibrilsmentioning
confidence: 91%
“…Hippocampal synaptic plasticity and memory were impaired at 8 months of age (46). A␤ protofibril levels correlate with spatial learning in AD transgenic mice expressing human APP with the arctic mutation (47) facilitating early intraneuronal A␤ aggregation (48). Despite the difficulty to compare the different studies on oligomeric A␤ species there seems to be converging evidence that they: 1) are primarily formed within neurons, 2) oligomeric A␤ species are more neurotoxic than monomeric or fibrillar A␤ in vitro, and 3) oligomeric A␤ species decrease synaptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…A␤ protofibrils have been identified as a toxic, soluble, and fibril-like intermediate in an in vitro A␤ fibrillization assay (22,23). It has been reported that A␤ protofibrils were detected in the brain and cerebrospinal fluid of APP transgenic mice using an antibody specific for A␤ protofibrils (42) and that passive immunization with the A␤ protofibril-specific antibody significantly reduced the amyloid burden in the brains of APP transgenic mice (43). In addition, it has been reported that E22G (Arctic) FAD mutation that alters an amino acid residue within A␤ region accelerates protofibril formation in vitro (20), as well as amyloid deposition in the brains of APP transgenic mice (44).…”
Section: Discussionmentioning
confidence: 99%